PENINGKATAN KEMAMPUAN PENGELOLAAN PENILAIAN KURIKULUM 2013 MELALUI PENDAMPINGAN BAGI GURU SEKOLAH DASAR - Nurkhan, Nurkhan (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2016)
The purpose of this study was to determine the success and effectiveness of the model of assistancein improving the management capacity assessment for elementary school teachers curriculumobjectives 2013. These investigators use techniques: lectures, discussions, drafting instruments,assessment practices. This mentoring models, proved successful and effective in improving theability of the management judging Goal Curriculum for elementary school teachers in 2013, it canbe proven by the data analysis showed no improvement, the average rose 28.7 points, or 23.9%.